Biological Therapies: Effects of Proinflammatory Pathways and their Inhibition on the Myocardium of Rheumatoid Athritis Patients - Obermair, Florian; Pieringer, Herwig (Current Medicinal Chemistry, 2015)
Background: The elevated risk of heart failure (HF) in rheumatoid arthritis (RA) is considered to be partly caused by the chronic low-grade systemic inflammation. As potent suppressors of inflammation, biologics were expected to influence HF development in RA. Unfortunately, case reports of HF in RA patients and non-RA HF studies have suggested that these drugs may even increase HF rates in RA. Aim: With this review we want to provide insight into the molecular mechanisms by which elevated cytokines, immune cell alterations and biologics influence myocardial function in RA patients. Beside preclinical data, clinical studies that assess the influence of biologics on HF development are reviewed. Results: Preclinical studies suggest a bidirectional role of the investigated cytokines (TNF-alpha, IL- 1, IL-6) on myocardial function. Common mechanisms of immune cell alterations in HF and RA have been observed in preclinical studies. High doses of infliximab in non-RA patients with HF were found to be harmful. The vast majority of retrospective studies suggest that TNF-alpha inhibitors do not increase the risk of HF development in RA patients. Nevertheless randomized controlled trials are missing and TNF-alpha inhibitors are contraindicated in RA patients with HF NYHA III/IV and should be used with caution in RA patients with HF NYHA I/II based on non-RA HF studies. Due to rare adverse events of HF, rituximab is contraindicated in RA patients with HF NYHA IV. Conclusion: Cytokines seem to have a bidirectional influence on HF development in RA. According to the published evidence it is unlikely that TNFalpha inhibitors substantially increase the risk of HF development in an RA population. Nevertheless they are contraindicated in RA patients with HF NYHA III/IV and should be used with caution in RA patients with HF NYHA I/II. The influence of anakinra, tocilizumab, rituximab and abatacept needs to be investigated in future studies.
Keywords: B-cells